Artificial intelligence in ociety: social, political and cultural implications of a technological innovation - Heinlein, Michael; Huchler, Norbert (Springer, 2024)
-- Understanding Artificial Intelligence in Society: Theoretical and Methodological Approaches -- Artificial Intelligence as Image and Myth -- Societal Risks and Social Dynamics of Artificial Intelligence -- The Politics of Artificial Intelligence -- Artificial Intelligence in the Workplace.